Pendidikan Agama Islam Berbasis Tiga Matra Pemberdayaan Sosial-Paritisipatif - Bakir Bakir ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2015)
This paper is to describe the recent challenge of Islamic education in schools, and to offer a new method for how Islamic education is possible to respons the challenge in the future. The decline of Islamic education is, among others, less of sensitivity over the complex social reality. This study would provide an idea of empowerment to students which is based on three dimensions of participation: power in, power with, and power within. These are implemented in the context of Islamic education in order to make sure student’s ability in working, either individually or collectively, without getting ride of moral spirituality as their basic values of human life.